2005
DOI: 10.1007/s10518-005-1241-3
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Piles during Earthquakes: Issues of Design and Analysis

Abstract: The seismic response of pile foundations is a very complex process involving inertial interaction between structure and pile foundation, kinematic interaction between piles and soils, seismically induced pore-water pressures (PWP) and the non-linear response of soils to strong earthquake motions. In contrast, very simple pseudo-static methods are used in engineering practice to determine response parameters for design. These methods neglect several of the factors cited above that can strongly affect pile respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The behavior of a pile foundation depends on the properties of the long, middle, and short piles [10,[24][25][26]. In this study, the pile analysis conditions used by Broms in 1964 were referred to (Table 2) [27].…”
Section: Pile and Structure Propertiesmentioning
confidence: 99%
“…The behavior of a pile foundation depends on the properties of the long, middle, and short piles [10,[24][25][26]. In this study, the pile analysis conditions used by Broms in 1964 were referred to (Table 2) [27].…”
Section: Pile and Structure Propertiesmentioning
confidence: 99%
“…The accuracy of the VERSAT-P3D code has been checked against more rigorous solutions obtained by the boundary integral method for harmonic-type excitations (Fan et al 1991). Finn (2005) has reported a back-analysis of the dynamic response of a single-pile prototype in a centrifuge test. He found that the code was capable of reproducing the observed behaviour at a reasonable level.…”
Section: Numerical Model For Dynamic Analysismentioning
confidence: 99%
“…Casolo et al [28] conducted comparative seismic vulnerability analysis on ten masonry towers to identify the factors that play a crucial role in their seismic vulnerability, while Hökelekli and Al-Helwani [40] investigated the effects of SSIs with infinite elements on the seismic damage behavior of stone masonry minarets with different soil types, considering the linear behavior of the soil domain. Several other studies also deal with the influence of soil-structure interactions on the fragility of buildings either on shallow or deep foundations [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%